ANALYSIS OF COMPONENTS INFLUENCING ECONOMIC GROWTH IN MATARAM CITY IN 2018 - 2023 - Januar Ferdiyansyah; Sahri, Sahri (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
Economic growth is an increase experienced by a region which indicates economic progress. This study aims to determine the effect of regional growth components on economic growth in Mataram City. The methodology used in this study is a quantitative method with shift share analysis and multiple regression analysis. The components that analyze shift share are regional share, proportional shift and differential shift. The data used in this study are secondary data, namely Gross Domestic Product by field of business from 2019 to 2023. Based on the results of the partial test study, it is known that the regional share component has a value of 0.000 which shows the influence of national policies on the economic growth of Mataram City. The proportional shift component has a value of 0.000, this shows that sectors that specialize quickly have a significant effect on the economic growth of Mataram City. The differential shift growth component has a value of 0.000, this shows the influence of the special power possessed by the region on the economic growth of Mataram City, this shows my influence. Meanwhile, based on the results of the simultaneous test, it shows that there is a joint influence of the regional share, proportional shift and differential shift components and the economic growth of Mataram City.